2019
DOI: 10.1177/1046496419876343
|View full text |Cite
|
Sign up to set email alerts
|

Individual Task Conflict Asymmetry and Peer Ratings of Member Effectiveness

Abstract: The present article explores the effects of individual task conflict asymmetry—a member’s task conflict perception relative to others on the team—on peer ratings of that member’s effectiveness. In two studies of student teams, we find that individuals who perceive more conflict than their teammates are rated as more effective team members. This effect is explained by uncertainty experienced by the high task conflict perceiver, which acts as a catalyst for additional effort expansion toward team goals. By turni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Furthermore, it is possible that, whereas RC asymmetry may be beneficial for the team, different individuals will fare differently. For example, members who are high perceivers of RC asymmetry, although benefitting the team, may feel, over time burned out from the responsibility or cognitive load that comes with occupying this space (Wang et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is possible that, whereas RC asymmetry may be beneficial for the team, different individuals will fare differently. For example, members who are high perceivers of RC asymmetry, although benefitting the team, may feel, over time burned out from the responsibility or cognitive load that comes with occupying this space (Wang et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At the conclusion of their work, Jehn and colleagues (2010) call for future studies to generate theory more explicitly regarding the isolated effects of RC asymmetry. While previous work has examined the effects of dispersion in task conflict (Wang et al , 2020) and generalized conflict (Jehn et al , 2010), their findings cannot necessarily be assumed to hold for RC asymmetry. The current framework isolates the effects of RC asymmetry and thus extends previous theory (Jehn et al , 2010) that address the topic of conflict asymmetry.…”
Section: Introductionmentioning
confidence: 96%
“…Finally, future research may also benefit from extending our paradigm to the individual-level by examining the effects of individual voice asymmetry. That is, drawing from conflict research (e.g., Jehn et al, 2010; Wang et al, 2019), scholars could conceptualize individual voice asymmetry , based on an individual’s voice contributions relative to the rest of their team, and assess its effects juxtaposed to the total amount of voice that individuals express. We expect voice asymmetry would have distinct effects on individual outcomes relative to overall voice levels, similar to the countervailing effects we found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although intrateam conflict can occur on the basis of task, relationship, and process concerns (Jehn, 1997; O’Neill et al, 2018), in the above illustration, it would seem plausible that members C and D are now engaging in relationship conflict with B, which would be characterized by anger and resentment toward B because of their weak performance. Recent work has suggested that intrateam conflict may not be a universal property of the team, such that it could be conceptualized as occurring within dyads or subgroups within a team (see Park et al, 2020; Wang et al, 2020). Because of this pattern of relationship conflict, C and D will likely consider the capabilities and resources that B brings to the team differently than from the initial meeting, and thus, their overall perceptions of the team’s efficacy will tend to differ from that of A and E. Thus, during teams’ lifecycles, members will tend to encounter disagreements, reducing the collective perceptions of the team’s shared confidence to successfully complete its project.…”
Section: Collective Efficacymentioning
confidence: 99%